The Relationship of Possessor and Possessed in German - Hidayat, E (KnE Social Sciences, 2019)
The relationship of possessor and possessed in German involve the aspects of the structure and meaning. The aspects of structure in terms of possessive construction are the internal noun phrases (NP) and the predicates used. The possessive constructions of the internal NP show the possessive relationship in German like Ulis Vater, das Dach des Hauses, die Tasche von Katrin and so on, as well as the behavior of the verbs haben and gehören like Eva hat ein Auto and das Buch gehört Ihm. Another interesting thing is to assess the type of possessive relationship based on the construction and semantic aspect, such as ownership, kinship relationship, whole-part relationship etc. This paper is intended to see the possessive relations and their constructions in German. Keywords: relationship, possessor and possessed, German